MANAJEMEN TENAGA PUSTAKAWAN SEKOLAH DALAM MENINGKATKAN KINERJA LAYANAN PERPUSTAKAAN DI SMAN HAMPARAN PERAK - Rizka Sabani; Rabukit Damanik; Usman Alhudawi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
School libraries play a strategic role as learning resource centers; however, their service performance relies heavily on how library personnel are managed. This study aims to describe the management of school library personnel, its impact on library service performance, and the strategic efforts undertaken to address existing obstacles at SMAN Hamparan Perak. The research is grounded in George R. Terry’s management theory encompassing the four functions of planning, organizing, actuating, and controlling and is further informed by a humanistic approach and the concept of emancipatory education. A qualitative, descriptive approach was employed. Data were collected through in-depth interviews, observation, and document analysis involving four informants the principal, library coordinator, library staff, and students and subsequently analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that while the four management functions are being implemented, challenges persist, including the coordinator holding dual roles, limited competency development, reliance on manual systems, and a lack of measurable performance evaluation. These conditions have resulted in a dual impact: positive outcomes such as orderly service and successful literacy programs, alongside negative ones such as limited collections and low student visitation rates. The school has implemented and continues to pursue various strategic measures to improve this situation. The study concludes that strengthening the management of library personnel is key to enhancing school library service performance.